EVALUATION OF BIOACTIVE COMPONENTS AND ANTIOXIDANT ACTIVITY OF VERNONIA ELAEAGNIFOLIA DC. (ASTERACEAE) IN GLYCOPHYTIC AND HALOPHYTIC CONDITIONS - M., JATHINA; K., ABDUS SALAM A. (International Journal of Current Pharmaceutical Research, 2020)
Objective: The investigate some of the antioxidant activities and bioactive potentials of Vernonia elaeagnifolia grown hydroponically in glycophytic and halophytic conditions. Methods: Plants were grown in Hoagland solution and subjected to (Sodium chloride (NaCl) treatments. Plants cultivated without salt stress served as the control. The phytochemical analysis was done with the help of Gas Chromatography-Mass Spectrometry (GC-MS) and antioxidants were analyzed following standard procedures using UV-Visible Spectrophotometer. Results: Significant changes were observed in the presence of antioxidants like superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPX), ascorbate peroxidase (APX), total polyphenols, proline and ascorbic acid. GPX and proline proved to be the major components in imparting salinity stress tolerance. The control showed the presence of 23 bioactive components while the treatment contained 19 components. Conclusion: The study thus provides information regarding the place of collection of the particular plant. Glycophytic conditions prove to be the best choice in terms of bioactive components and fatty acid contents. The investigations reveal that the plant contains several bioactive components and antioxidants, which prove it as a promising plant for developing potential drugs.